An Experimental Study of Flow Behavior of Coiled Tubing Drilling System. (29th May 2014) - Guan, Feng; Ma, Weiguo; Tu, Yiliu; Zhou, Chuanxi; Feng, Ding; Zhou, Bo
Abstract : Coiled tubing drilling has become an important development direction of drilling. The method of combining theoretical calculation with the experimental verification is adopted to analyze the flow of the coiled tubing drilling system. A set of experimental bench is developed, three kinds of curvature ratio of coiled tubing are used, and the frictional pressure losses of coiled tubing and partial pressure drop of each downhole tool are tested. The results of experiments with water agree well with rough pipe calculation model. The pressure losses of coiled tube are obviously larger than that of straight tube, and the value of it is about 11–17%. The larger the curvature ratio is, the more the pressure losses of coiled tubing are. The fluid experiment with the polymer presents obviously the drag reduction effect. Experiment of simulated bottom hole assembly shows that partial pressure drop of bottom hole assembly is large. It has a little effect on the pressure losses of coiled tubing when whole bottom hole assemblies are connected. The research results can be used as the basis for formulating coiled tubing drilling process parameters, which will provide a guide for engineering practice.